The Implementation of Multiple Intelligence-Based School Management - Fajarwati, Dian; Raharjo, Tri Joko; Samsudi, Samsudi (The Journal of Educational Development, 2016)
This study investigates the implementation of school management which accommodates the potential intelligence of each student in order to foster the quality of education in Indonesia.The concept of Multiple Intelligencesis in accordance withRI Act. No. 20 of 2003 on National Education System listed in Chapter I of Article 1, paragraph 1, which states that Education is a conscious and deliberate effort to create an atmosphere of learning and learning process so that learners are actively developing their potential to have the spiritual power on religion, self-control, personality, intelligence, noble character, and acquiring necessary skillsfor the societyand nation.Multiple Intelligences-based school management takes into account the potential of studentsâ potentials in accordance with various intelligences. Management will be successful if the management significantly concerns withthe stage of inputs, processes, outputs, and outcomes. This is necessary for an effective school management model based on the concept of Multiple Intelligences starting from the input, process, output and outcome.